Knowledge attitude and practice regarding prevention of needle stick injuries among nursing students in Henan province, China - Dongyang Wang; Amornrat Anuwatnonthakate; Kessarawan Nilvarangkul (Journal of the Pakistan Medical Association, 2021)
Objective: The purpose of study was to identify the knowledge, attitude and practice of prevention NSIs among nursing students in Henan province, China. Methods: A cross-sectional study of 400 nursing students in 7 nursing education institutes in Henan province during June to July 2019 was performed. Structured questionnaires were used to assess participants’ knowledge, attitudes and practices of prevention NSIs. Chi-square tests were used to assess correlations between variables. Multivariate regression analysis was used to test the factors related to prevention NSIs. Results: It has shown that 67% of nursing students suffered at least one NSI during their internship. The most common cause of injury was the injection process, the venous catheter management process, and the disposing all kinds of needle waste process (p<0.05). Female students showed more than three times greater chance of intentionally breaking needle after injection (OR 2.50, 95%CI 1.03-6.08). Capping needles always used by two hand (OR 0.40, 95%CI 0.19-0.85) and separating the needle from the syringe by hand after injection (OR 0.23, 95%CI 0.16-0.57) were negatively related to bachelor students. Conclusion: Nursing students show high prevalence of NSIs and lack of prevention knowledge, attitude, and practice. It’s necessary to develop and increase occupational safety protection courses and establish regulations for the prevention of NSIs. Continuous...